Interdiscurso e intertextualidade na imprensa escrita: análise de crônicas jornalísticas do caderno Ilustrada do jornal Folha de S. Paulo - Prado, Losana Hada de Oliveira (2014)
The objective of this research is to reflect about the interdiscourse and intertextuality in the constitution of the chronicles journalistic writing. Based on the relation between the different planes of discourse, including intertextuality, the intention is to verify the space exchange (interdiscourse) preceding the genesis of discourses present in the chronicles. For this, the study of global semantic, by applying different textual clues, is taken as evidence that helps to understand the functioning of interdiscourse. The theoretical framework of the research are included in Literary Theory, in Textual Linguistics, French Discourse Analysis and more specifically in-discursive enunciation proposed by Dominique Maingueneau in Genesis of Discourse (2007). His theory is the basis for the analysis of a discursive practice which are imbricated verbal and non-verbal, the text that constitute the chronic and the image that dialogues to the speech of this genre. According to the principle of the Global Semantic, the discourse must be taken in the multiplicity of its dimensions. Based on that premise, the initial hypothesis of this thesis is: 1) There is a set of restrictions that are specifics of the genre analyzed; 2) The interdiscourse and intertextuality are principles that rule the verbal-visual textualization of the chronicles and journalistic; 3) it is not possible to separate the operation of interdiscourse of its materialization in the order of the language. The corpus of reference of the research consists of seven journalistic chronicles of the newspaper Folha de S. Paulo, between the months of June and July during the South Africa World Cup in 2010. This research has pervaded also a corpus of intersemiotic nature, however, it was considered that is not possible to endorse one idea over another. It is possible to enlace them in the same movement, which implies to claim that the meaning or meanings are not in a specific section of the text. They are in directions that emanate from set and organized according to the same rule set, the global semantics